Parental Education Conditions in Rural Areas of Bengkulu: Case Study on Responsive Gender, Parenting Styles, Equality Behavior, and Learning Needs - Ari Putra (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
This study is to examine the understand the awareness and knowledge of the community in these areas regarding gender issue, which crucial for informing government policies on community education. This scientific paper employs a qualitative approach to comprehensively describe the nuanced experiences of parental education in Bengkulu, Indonesia. The research was conducted in three rural area Bengkulu Province located on Sumatra Island, Indonesia. parental education in rural areas is hindered by persistence of traditional gender roles that assign distinct responsibilities to women and men. the study revealed that there are distortions in the community understandings of gender in rural Bengkulu. The distortions manifest as a lack of awareness and understanding of gender issues, resulting in inadequate child-parent interaction, especially among fatherless families, perpetuation of gender stereotypes and a deficiency in gender-responsive literacy. The findings indicate that parental education in rural areas is hindered by persistence of traditional gender roles that assign distinct responsibilities to women and men. Understanding the condition of parental education and gender responsiveness in rural Bengkulu is very important because it is directly related to government policy making in the field of public education. This report highlights the importance of promoting gender equality, combating stereotypes, and improving parent education in rural areas to create a more inclusive and responsive educational environment.